The interactive effect of demographic and clinical factors on hippocampal volume: A multicohort study on 1958 cognitively normal individuals. Issue 6 (10th April 2017) - Ferreira, Daniel; Hansson, Oskar; Barroso, José; Molina, Yaiza; Machado, Alejandra; Hernández‐Cabrera, Juan Andrés; Muehlboeck, J‐Sebastian; Stomrud, Erik; Nägga, Katarina; Lindberg, Olof; Ames, David; Kalpouzos, Grégoria; et al.
Abstract: Alzheimer's disease is characterized by hippocampal atrophy. Other factors also influence the hippocampal volume, but their interactive effect has not been investigated before in cognitively healthy individuals. The aim of this study is to evaluate the interactive effect of key demographic and clinical factors on hippocampal volume, in contrast to previous studies frequently investigating these factors in a separate manner. Also, to investigate how comparable the control groups from ADNI, AIBL, and AddNeuroMed are with five population‐based cohorts. In this study, 1958 participants were included (100 AddNeuroMed, 226 ADNI, 155 AIBL, 59 BRC, 295 GENIC, 279 BioFiNDER, 398 PIVUS, and 446 SNAC‐K). ANOVA and random forest were used for testing between‐cohort differences in demographic‐clinical variables. Multiple regression was used to study the influence of demographic‐clinical variables on hippocampal volume. ANCOVA was used to analyze whether between‐cohort differences in demographic‐clinical variables explained between‐cohort differences in hippocampal volume. Age and global brain atrophy were the most important variables in explaining variability in hippocampal volume. These variables were not only important themselves but also in interaction with gender, education, MMSE, and total intracranial volume. AddNeuroMed, ADNI, and AIBL differed from the population‐based cohorts in several demographic‐clinical variables that had a significant effect on hippocampal volume. Variability in hippocampal volume in individuals with normal cognition is high. Differences that previously tended to be related to disease mechanisms could also be partly explained by demographic and clinical factors independent from the disease. Furthermore, cognitively normal individuals especially from ADNI and AIBL are not representative of the general population. These findings may have important implications for future research and clinical trials, translating imaging biomarkers to the general population, and validating current diagnostic criteria for Alzheimer's disease and predementia stages.